2015
DOI: 10.1371/journal.pone.0139842
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and Concussion in Juvenile Rats: Examining Molecular and Structural Aspects of the Frontostriatal Pathway

Abstract: Impulsivity and poor executive control have been implicated in the pathogenesis of many developmental and neuropsychiatric disorders. Similarly, concussions/mild traumatic brain injuries (mTBI) have been associated with increased risk for neuropsychiatric disorders and the development of impulsivity and inattention. Researchers and epidemiologists have therefore considered whether or not concussions induce symptoms of attention-deficit/hyperactivity disorder (ADHD), or merely unmask impulsive tendencies that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Mild traumatic brain (mTBI) injury in rats was also found to have complex effects on executive function that varied by sex. mTBI led to more impulsive errors in the 5CSRTT in control males; however, more impulsive errors were identified only in females when examining offspring from nutrient-restricted dams [114], indicating that early life environment can also establish a sexdependent risk profile for future insults.…”
Section: Programmingmentioning
confidence: 84%
See 1 more Smart Citation
“…Mild traumatic brain (mTBI) injury in rats was also found to have complex effects on executive function that varied by sex. mTBI led to more impulsive errors in the 5CSRTT in control males; however, more impulsive errors were identified only in females when examining offspring from nutrient-restricted dams [114], indicating that early life environment can also establish a sexdependent risk profile for future insults.…”
Section: Programmingmentioning
confidence: 84%
“…In the PFC, it is primarily excitatory synapses that are targeted for elimination [136]. Synaptic pruning is a key developmental process, as deficits in synaptic function are linked to neurodevelopmental disorders [137,138] and executive function deficits [114]. Further, executive function deficits have been suggested to relate to more subtle changes in neural function or microstructure rather than gross changes in neuron number or morphology [138].…”
Section: Programmingmentioning
confidence: 99%
“…Likewise, in individuals with CTE symptoms, similar phenotypic manifestations have been reported as the condition progresses (Omalu et al, ). Results from the studies assessed here indicate increased anxiety and impaired attention (Hehar, Yeates, Kolb, Esser, & Mychasiuk, ; Wang et al, ; Yamakawa, Salberg, et al, ). There was also a consistent depression‐like response to the forced swim task in mTBI groups, as evidenced by immobility and disinclination to swim (Salberg et al, ).…”
Section: Discussionmentioning
confidence: 69%
“…Studies in rodent models with early, prepubescent traumatic brain injuries have revealed sexually dimorphic remodeling that persists into adulthood, possibly due to differences in brain maturation trajectories . The onset of WM volume changes may be occurring outside of the critical period in female subjects allowing appropriate compensation for early damage .…”
Section: Discussionmentioning
confidence: 99%